Dramaturging The Tempest: A Pedagogical Forum. (12th February 2014) - Kelly, Philippa
<x content-type="archive" xml:space="preserve">Abstract</x> "Dramaturging The Tempest: A Pedagogical Forum, " uses dramaturgy—the interface between research and its practical application in the theatre—as a way of preparing The Tempest for a college course curriculum. The article aims to show instructors how to teach dramaturgy as an explication of The Tempest and how to use The Tempest as a means of teaching dramaturgy. The objective is for students to emerge from the course conversant in how to be dramaturgs in the preparation of a professional production. Dramaturgy also illuminates the highly metadramatic underscoring of The Tempest, a play that constantly invites its own characters to be audience to, and critics of, Prospero's carefully constructed "worldview." My brief for this journal issue is to write an essay on The Tempest that can be used as an explication de texte for teaching postcolonial studies. As a practicing dramaturg, I've decided to focus on postcolonial dramaturgy. What does a dramaturg do? What can be gained from dramaturgical teaching, and how is it prepared for? What skills will students develop?